Quality investigation of frozen garden strawberries at partial dehydration before freezing - Zamorska, Iryna; Zamorskyi, Volodymyr; Halahur, Yuliya; Osyka, Viktor; Belinska, Svitlana; Motuzka, Iuliia; Bozhko, Tetiiana; Krasulya, Olena; Fil, Mariia (Zamorska I. Quality investigation of frozen garden strawberries at partial dehydration before freezing / I. Zamorska, V. Zamorskyi, Y. Halahur, V. Osyka, S. Belinska, I. Motuzka, T. Bozhko, O. Krasulya, M. Fil //EUREKA: Life Sciences. – 2020. – № 1. – P. 11-17, 2020)
Garden strawberry is an important berry culture, consumed fresh and frozen. But a quality of frozen berries is not always at the high level because of changing organoleptic properties, tissues structure and biological active substances losses. It motivates searches for different methods of previous processing of berries before freezing. There was used a production technology of frozen strawberry with partial dehydration before freezing for solving the problem. It has been established, that frozen strawberries, partially dehydrated before freezing, saved by 0.2–0.3 % more dry soluble substances, by 0.2 % – sugars, by 7.0–7.9 % – ascorbic acid at a practically equal level of organic acids. The organoleptic mark of frozen partially dehydrated strawberries was by 0.2–0.3 points higher against the control. Among the studied varieties of strawberry, Polka berries got a mark higher by 0.2–0.9 points. Садова полуниця - важлива ягодна культура, вживається в свіжому і замороженому вигляді. Але якість заморожених ягід не завжди на високому рівні через зміну органолептичних властивостей, структури тканин та втрати біологічних активних речовин. Це мотивує пошук різних методів попередньої обробки ягід перед заморожуванням. Для вирішення проблеми була використана технологія виробництва замороженої полуниці з частковою дегідратацією перед заморожуванням. Встановлено, що заморожена полуниця, частково зневоднена перед заморожуванням, зберігає на 0,2–0,3% більше сухих розчинних речовин, на 0,2% - цукрів, на 7,0–7,9% - аскорбінову кислоту практично на рівні рівня органічних кислот. Органолептична марка замороженої частково зневодненої полуниці була порівняно з контрольною на 0,2–0,3 бала. Серед досліджених сортів полуниці ягоди польки отримали відмітку на 0,2–0,9 бала.
Keywords: strawberries; полуниці; partial dehydration; часткове зневоднення; freezing of garden strawberry; заморожування садової суниці; кафедра технології молока і молочних продуктів